Digital Image Compression and Decompression Using Three Different Transforms and Comparison of Their Performance - Sathyanarayana, Pabbisetti; R Saeedipour, Hamid (2006)
Data compression is an important tool in digital image processing to reduce the burden on the storage and transmission systems. The basic idea of data compression is to reduce the number of the image pixel elements directly, say by sampling, or by using transforms and truncate the transformed image coefficients, so that the total number of picture elements or its coefficients are reduced.